Association of vitamin D with adiposity measures and other determinants in a cross-sectional study of Cypriot adolescents - Kolokotroni, Ourania; Papadopoulou, Anna; Yiallouros, Panayiotis K.; Raftopoulos, Vasilios; Kouta, Christiana; Lamnisos, Demetris; Nicolaidou, Polyxeni; Middleton, Nicos (My University, 2015)
Objective to assess vitamin D status among Cypriot adolescents and investigate potential determinants including BMI and body fat percentage (BF%).Design Participants had cross-sectional assessments of serum vitamin D, physical activity, dietary vitamin D intake and sun exposure. Linear and logistic regression models were used to explore the associations of vitamin D with potential predictors.Setting Hospitals, Cyprus, November 2007–May 2008.Subjects Adolescents (n 671) aged 16–18 years.Results Mean serum vitamin D was 22·90 (sd 6·41) ng/ml. Only one in ten children had sufficient levels of vitamin D (≥30 ng/ml), while the prevalence of vitamin D deficiency (12–20 ng/ml) and severe deficiency (<12 ng/ml) was 31·7 % and 4·0 %, respectively. Lower vitamin D was associated with winter and spring season, female gender, reduced sun exposure in winter and darker skin. Participants with highest BMI and BF% when compared with a middle reference group had increased adjusted odds of vitamin D insufficiency (OR = 3·00; 95 % CI 1·21, 7·45 and OR = 5·02; 95 % CI 1·80, 13·97, respectively). A similar pattern, although not as strong, was shown for vitamin D deficiency with BF% (OR = 1·81; 95 % CI 1·04, 3·16) and BMI (OR = 1·51; 95 % CI 0·85, 2·67). Participants in the lowest BMI and BF% groups also displayed compromised vitamin D status, suggesting a U-shaped association.Conclusions Vitamin D deficiency in adolescence is very prevalent in sunny Cyprus, particularly among females, those with darker skin and those with reduced sun exposure in winter. Furthermore, vitamin D status appears to have a U-shaped association with adiposity measures.
Keywords: Vitamin D; Adolescents; Predictors; Adiposity; BMI; Body fat percentage